The Modern methods of obesity treatment - review of the literature - Zygmunt-Siembida, Ewelina; Wróblewska, Hubert; Zimna, Aleksandra; Wróblewska, Kinga; Kozdra, Magdalena; Piasek, Laura; Osińska, Aleksandra (Quality in Sport, 2023)
Introduction and aim of the study: Obesity is not only increases the risk of developing other diseases, but is itself a chronic disease. It is characterized by a lack of tendency to spontaneous resolution and a tendency to relapse. The growing number of patients facing obesity and its consequences prompts the search for newer and newer methods of its treatment. The aim of this paper is to discuss modern methods of obesity therapy, aimed at reducing the risk of its consequences, both health, psychological, social and economic. Methods and materials: This literature review is based on articles published in the PubMed database from 2016 to 2023, using the following phrases: "obesity risk factors", "obesity treatment", "diagnosis of obesity", "GLP -1 obesity". State of knowledg: We now know that obesity is a disease that needs to be treated. The goal of therapy is not only to achieve the target body weight, but also to reduce the risk of disease and improve the control of coexisting diseases. Conclusion: Obesity is a disease that requires interdisciplinary treatment based on behavioral therapy including changing the lifestyle to a healthier one, psychological support and pharmacological, and in some cases, surgical treatment.